Henry H. Shepard correspondence - Shepard, Henry H.
Letters written by Shepard during his Civil War service with the 9th Iowa Infantry Regiment to a friend, Henry D. Marsh, Swain, N.Y., describing camp life, troop movements, and battles in Alabama, Arkansas, Georgia, Louisiana, Mississippi, Missouri, and Tennessee.
Union army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Marsh, Henry D. -- Correspondence; United States. -- Army -- Military life; United States. -- Army. -- Iowa Infantry Regiment, 9th (1861-1865); Alabama -- History -- Civil War, 1861-1865.; Arkansas -- History -- Civil War, 1861-1865.; Georgia -- History -- Civil War, 1861-1865.; Louisiana -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; Missouri -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Soldiers